Approach for combining spacecraft attitude and thermal control systems - Varatharajoo, Renuganth; Kahle, Ralph; Fasoulas, Stefanos (American Institute of Aeronautics and Astronautics, 2003)
Coupling of existing spacecraft subsystems could be an alternative to reduce the emerging cost, decrease the system volume/mass and complexity, increase the reliability, and enhance the overall performance of future spacecraft. Therefore, a new concept to combine the attitude and thermal control systems is presented. The concept is based on electric conducting fluids used in a closed loop for the attitude and thermal control systems. The potential coupling is discussed for two alternative setups incorporating electromagnetic pumping and thermoelectric phenomena, respectively. The corresponding equations are derived and the end-to-end system demonstration is performed. The results demonstrate that the new concept could replace the existing subsystems using current available technology, especially the thermoelectric option, when used as a combined attitude actuator and thermal radiator.